Drafting commercial agreements - Christou, Richard (Sweet & Maxwell/Thomson Reuters, 1993)
Commentary on, and provision of, precedents for use by the commercial practitioner advising clients on a range of business transactions. Includes all the most common transactions with related precedents grouped at the end of each chapter. CD-rom also contains all the precedent material